Fostering critical thinking skills in geography education: An authentic assessment model using field-lab approach - As’ari Ruli; Rosali Ely Satiyasih; Mulyanie Erni (E3S Web of Conferences)
This research focuses on fostering critical thinking skills in geography education through an authentic assessment model with a field lab approach. This research was used as a case study at Siliwangi University. Critical thinking is essential in geography education because it empowers students to analyze complex spatial phenomena, make decisions, and contribute effectively to society. This research answers the need for innovative assessment methods that are in line with the importance of critical thinking in geography education. This research method focuses on developing critical thinking skills through an authentic assessment approach using field laboratory methods. This research uses an experimental research design by applying quasi-experimental methods in a geography learning environment. The approach used is a qualitative approach to analyze the impact of authentic assessment models on the development of students’ critical thinking skills. Findings study shows that the application of an authentic assessment model with a field-lab approach in geography education has shown promising results in improving students’ critical thinking abilities. This authentic assessment model allows students to be actively involved in the learning process and apply their knowledge and skills in real-world contexts.